The effects of melatonin against atherosclerosis-induced endothelial dysfunction and inflammation in hypercholesterolemic rats - Sezgin, Dilsad; Aslan, Gulnur; Şahin, Kazım; Tuzcu, Mehmet; Ilhan, Necip; Sahna, Engin (Taylor & Francis Ltd, 2023)
The aim of this study was to investigate the effects of melatonin on the serum asymmetric dimethylarginine (ADMA) levels and the expressions of vaspin, visfatin, dimethylarginine dimethylaminohydrolase (DDAH), and signal transducer and activator of transcription-3 (STAT-3) for evaluation of endothelial function and inflammation in the hypercholesterolemic rats. Rats were divided into 5 groups: (1) control, (2) hypercholesterolaemia, (3) melatonin administrated concurrently with cholesterol diet, (4) melatonin administrated only last 2 weeks and fed with cholesterol diet, (5) atorvastatin administered only last 2 weeks fed with cholesterol diet. Although an increase was observed in the expressions of visfatin and STAT-3 and the serum ADMA levels, the vaspin and DDAH protein expressions were found to decrease with hypercholesterolemic diets. Melatonin was determined to restore all the parameters to the normal levels. In conclusion, melatonin may have protective and therapeutic effects on hypercholesterolaemia by regulating vaspin, STAT-3, DDAH, and ADMA signalling pathways and create similar effects with atorvastatin.
Keywords: Melatonin; vaspin; visfatin; STAT-3; ADMA